Propuesta Metodológica para Estimular el Desarrollo de la Lateralidad en los niños de 3 a 4 años de Educación Inicial en la Unidad Educativa Marco A. Subía Batalla de Panupali. - Banda Yánez, Nelly Catalina (2020)
The purpose of this research is to diagnose how poorly defined laterality can influence in the learning process, for this reason a proposal of methodological strategies was done to stimulate the development of laterality for children from 3 to 4 years of Initial Education Marco Aurelio Subía Batalla de Panupali Educational Unit. The methodology used in the research is non-experimental, because it is based directly on scientific content, it will be treated from the quantitative approach, because the information about the problem determined was collected through research instruments that made it possible to obtain data real that allowed to develop an appropriate study and determine the feasibility, by the other hand there was adequate and necessary bibliography, which supports the research. The same that allowed to verify the psychomotor learning processes alterations. For this reason, it is necessary to apply methodological strategies based in the laterality stimulation development at an early ages which directly benefits children. Therefore, in conclusion it is important that teachers have available an instrument that allows them to develop the teaching-learning processes in an effectively way and based on obtaining favorable results in the integral development of children